Characteristics and agronomic performance of wheat cultivar BRS 229 in Paraná State, Brazil - Brunetta, Dionisio; Bassoi, Manoel Carlos; Dotto, Sergio Roberto; Scheeren, Pedro Luiz; Miranda, Martha Zavariz de; Tavares, Luiz César Vieira; Miranda, Luiz Carlos (Pesquisa Agropecuaria Brasileira, 2006)
The wheat cultivar BRS 229, released for the State of Paraná, has a gluten strength suitable for baking. The cultivar is moderately resistant to wheat blast and spot blotch, and it is also moderately susceptible to leaf rust, powdery mildew, wheat soilborne mosaic and scab. The cultivar belongs to the medium maturity group, presents moderate resistance to lodging and tolerance to aluminum toxicity. In the State of Paraná, in five years of yield testing, BRS 229 presented a grain yield average of 4,633 kg ha-1, in the region 6 (north); 3,233 kg ha-1, in the region 7 (west-central and west); and 4,349 kg ha-1, in the region 8 (south).